Pluralism and truth - Holguín, Magdalena (Estudios de Filosofía, 2008)
In this presentation I present some of Wittgenstein's reflections to show that, even though the rational project of grounding knowledge on absolute truths is, in fact, unrealizable, there would be a way of understanding the concept of truth that does not imply a personal or cultural relativism but, on the contrary, excludes it. [Fragment]